ON FUZZY-⨁-S-MODULES - Majid M. Abed (مجلة جامعة الانبار للعلوم الصرفة, 2018)
A module M is a ⨁-Supplemented if M=⨁Ni such that Ni is a direct summand of M. In this paper we introduce the notion of Fuzzy ⨁-Supplemented Module (Fuz-⨁-S-Mod) as a generalization of ⨁-supplemented module. We investigate several characterizations and properties of this concept. Moreover we investigated several relationships among Fuz-⨁-S-Mod and other Fuzzy concepts such as fuzzy D1-module (Fuz-D1-module), Fuzzy Lifting Module (Fuz-L-mod) and Amply Fuzzy Supplemented module (A-Fuz-S-mod) are studied.